ANALYSIS OF THE UTILIZATION OF VINA MAULINA CONTENT IN THE CAREER FIELD ON THE TIKTOK APPLICATION AS A LEARNING MEDIA - Rezky Hasanah Harianja; Bayu Syahputra Syahputra (Djtechno: Jurnal Teknologi Informasi, 2025)
This study analyzes the utilization of Vina Maulina's educational content on the TikTok platform as a learning medium for young people's career development. This research focuses on System Quality, Information Quality, Content Quality, and Learning Effectiveness variables that influence how effective audience learning is. Data collection was done by distributing questionnaires with 200 respondents. Data was collected from college students aged 20-24 years old through qualitative-based descriptive method and SEM (Structural Equation Modeling) approach. The result shows that the three independent variables significantly increase the effectiveness of learning. The content created by Vina Maulina in an informative, interesting, and relevant way can help audiences learn more about their careers and motivate them to achieve their goals. TikTok can be a creative platform that educates and entertains, especially for educating the younger generation about the world of work. In addition, Vina Maulina's engaging and accurate content, including career tips, motivation, and success strategies, is proven to motivate audiences to reach their full potential.